Project Productivity vs. Health & Safety - Wilson, Stephen (2008)
Health and Safety often has a negative perception among project managers who operate in high pressure environments where high levels of productivity are demanded from Management. The level of procedures that must be followed and the associated bureaucracy are often seen as having an impeding effect on completing work in the most optimum way possible. Many studies have been conducted to further investigate this theory, with mixed results. Ideologies such as Total Safety Management (TSM) which borrows its theories heavily from Total Quality Management (TQM) have been shown to have a substantial positive effect on health and safety performance while boosting productivity as a by-product. Other approaches which have been the victim of poor implementation or poor management have be seen to further the theory that increased focus on safety management can impede a company’s ability to operate at its most efficient with respect to productivity. This study investigates two Companies operating in the Oil & Gas Industry in the UAE, over a five year period to assess the impact on productivity that their Health and Safety prioritised approach had on productivity. Company A adopted a proactive intensive Health and Safety Management approach immediately prior to the 5 year period while Company B revised their approach to a more in depth safety management outlook midway through the five year period. Research was undertaken at both of these Companies by studying their productivity performance figures against their accident reporting statistics. Surveys and interviews with each Company’s workforce were also conducted to measure the intangible factors from a behavioural and psychological approach towards the new safety management systems adopted by each company. It was found in both cases that the improved safety management approaches had a great effect on the workforce both in improving accident reporting statistics matched by significant gains in productivity. The outcome of the surveys also supported this showing great increase in the perception of safety in the work place and increased levels of motivation and good feeling towards the management of each Company. It can be seen that if implemented correctly and with the visible support of senior management, adopting a safety focused approach towards a productivity and projectised environment that increased safety on site can lead to improved productivity rather than the opposite. Further research is required into this vast field for a better behavioural and psychological understanding of the benefits of positive proactive safety management. There is also a large scope for further research into finding the most optimal management and implementation methods of a new safety managements system to provide a guide for companies looking to revise their safety management approach in the future.